Implementation of an Inclusive and Creative Approach as Curriculum Enrichment for Early Childhood Education with Special Needs - Priyanti, Nita; Setiawan, Imam (Journal of Early Childhood Education (JECE), 2024)
Children with special needs require an inclusive and diverse approach for education to supporting their optimal development. Sekolah Alam Atifa is an educational institution with a nature-based learning concept, offers a holistic and fun learning experience. Its main objective is to improve the social, motor, cognitive and critical thinking skills of children with special needs through gardening and small farming activities. This research used a qualitative approach with a case study design. The research participants consisted of 10 children with special needs aged 4-7 years at Atifa Nature School. Curriculum Enrichment through Gardening and Little Farm are implemented in the daily education program, involving activities such as planting and caring for plants, raising small animals, and learning the life cycle of nature. The implementation of Curriculum Enrichment through gardening and “Little Farm” at Atifa Nature School shows a positive impact on children with special needs. They experienced an increase in skills, children's motor abilities also improved. Cognitively, children gained a better understanding, developed a sense of responsibility, confidence, and perseverance and improved in critical thinking. This implementation can be adopted by other educational institutions to support the development of children with special needs in a holistic and inclusive manner.